2020
DOI: 10.1177/1359105320916541
|View full text |Cite
|
Sign up to set email alerts
|

“I’ll work out tomorrow”: The Procrastination in Exercise Scale

Abstract: Exercise procrastination (i.e. the voluntary delay of intended exercise) represents a novel, reasoned route to self-regulatory failure in physical activity. This study sought to develop and evaluate a scale to measure exercise procrastination and assess its relationship with self-reported physical activity. Two surveys were administered to community samples ( n = 270, 279). In both samples, the Procrastination in Exercise Scale was positively correlated with general procrastination and predicted lower physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Research over the past two decades has documented that procrastination can also have wide-ranging and negative consequences for health and well-being [ 3 ], especially when it becomes a chronic behavioural pattern. For example, procrastination is associated with higher stress [ 4 , 5 , 6 , 7 , 8 , 9 ], use of less adaptive coping strategies [ 10 ], poor health behaviours [ 5 , 9 , 11 , 12 , 13 ], poor quality sleep [ 14 , 15 ], poor self-rated health [ 16 ], and a greater number of physical illnesses and symptoms [ 6 , 9 , 12 , 17 ].…”
Section: Procrastination and Stress: A Conceptual Review Of Why Conte...mentioning
confidence: 99%
“…Research over the past two decades has documented that procrastination can also have wide-ranging and negative consequences for health and well-being [ 3 ], especially when it becomes a chronic behavioural pattern. For example, procrastination is associated with higher stress [ 4 , 5 , 6 , 7 , 8 , 9 ], use of less adaptive coping strategies [ 10 ], poor health behaviours [ 5 , 9 , 11 , 12 , 13 ], poor quality sleep [ 14 , 15 ], poor self-rated health [ 16 ], and a greater number of physical illnesses and symptoms [ 6 , 9 , 12 , 17 ].…”
Section: Procrastination and Stress: A Conceptual Review Of Why Conte...mentioning
confidence: 99%
“…Procrastination, referred to an irrational delay of intended actions, is a widespread problem that hinders our work process (Metin et al, 2018), academic achievement (Balkis, 2013), and pursuit of a healthy lifestyle (Kelly & Walton, 2021). As a survey showed, 65% of adult respondents reported high procrastination in at least one life domain like career, education, health, or finance, and 25% of respondents procrastinated in four or more life-domains (Hen & Goroshit, 2018).…”
mentioning
confidence: 99%
“…Some studies have already shown this (negative) impact of procrastination on health-promoting behaviour, e.g. going to bed on time (Kroese et al, 2014(Kroese et al, , 2016Rapoport et al, 2023) or exercise regularly (Kelly & Walton 2021;Klingsieck & Weigelt, 2016;Rapoport et al, 2022). It has been shown that high procrastinators exercise less than they intended to, sleep less, do not keep to their scheduled bedtimes, and generally report more health problems.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, special questionnaires were developed in these areas to assess domainspecific procrastination. In the area of bedtime procrastination, there is the Bedtime Procrastination Scale by Kroese et al (2014), and for sports, there are the questionnaires by Klingsieck and Weigelt (2016) and by Kelly and Walton (2021). Haghbin and Pychyl (2016) also developed the Exercise and Healthy Diet Procrastination Scales.…”
Section: Introductionmentioning
confidence: 99%